Holistic Flexibility for Deploying Systems Thinking as a Cognitive Ski ll - Chowdhury, Rajneesh (Systemic Practice and Action Research, 2023)
Considering Systems Thinking (ST) as a cognitive skill can create grea ter acceptability of and openness to the discipline from practitioners and researchers outside operations research and management science. R ather than associating ST with frameworks and methodologies, ST as a c ognitive skill can help popularize and democratize the discipline. Thi s paper highlights how the conceptual lens of Holistic Flexibility can help practitioners deploy ST as a cognitive skill without the applica tion of any traditional systems methodology. Holistic Flexibility is d efined as the dynamic interplay between a state of mind that has the a bility to absorb systemic complexity and a state of practice that has the ability to embrace flexibility, both in intent and in form. Throug h two case-studies, discussions in this paper highlight how Holistic F lexibility can serve as a conceptual lens for systems practitioners. T he case-studies demonstrate the importance of a practitioner’s ability to seamlessly manage and work with multiple variables, stakeholders, and factors to deliver responsible outcomes with the aid of learning l oops. The main contribution of this paper lies in the case-studies and analyses presented that provide use cases for Holistic Flexibility in ST, which will help address recent calls in the discipline for ST to be considered as a cognitive skill.